African-American female administrators at predominantly White institutions in Tennessee: Is There a Need for Affirmative Action? - Howard , Barbara (Journal of Interdisciplinary Studies in Education, 2017)
With recent attention given to affirmative action and race relations, the purpose of this research was to revisit a previous study made in 2001 and determine if there was a need for further attention to African-American female administrators at Predominantly White Institutions (PWIs) in Tennessees. A review of data in 2015 show at Middle Tennessee State University, 6.4% of positions classified as executive/administrative were held by African-American females compared to 35% White females and 51.3% White males. At the University of Memphis, 18.9% African-American females were in executive/administrative/managerial positions compared to 31% for White females. At the University of Tennessee, 9.5 % of the executive/administrative/managerial positions were held by African Americans (both males and females). Data show, at the very least, a decline in the disaggregating of data for African-American female administrators. Data also show low numbers and percentages of African-American females in executive or managerial roles in year 2015.